PENGARUH GAYA KEPEMIMPINAN, EMPATI DAN MOTIVASI TERHADAP BUDAYA ORGANISASI (Studi Kasus Terhadap Kepala Sekolah Dasar Kota Gorontalo) - Novianty Djafri (Jurnal Manajemen., 2015)
Purpose of the study to determine the effect of leadership style, empathy, and motivation of on the organization culture as the principal basis of Gorontalo city. The study object is the subject of elementary school principals as many as 55 people. Four variables of the data gathered through the research questionnaire instrument valid and reliable. Statistical analysis of research data using path analysis with significance in accordance with the output of spss 22.0 Findings of this study indicate that there is a positive direct effect of leadership style, the principal emphaty, motivation toward school organizational culture. There is a direct positive leadership style of emphaty and motivation principals.